A decade of crystallization drops: Crystallization of the cbb3 cytochrome c oxidase from Pseudomonas stutzeri. (4th February 2014) - Buschmann, Sabine; Richers, Sebastian; Ermler, Ulrich; Michel, Hartmut
Abstract: The cbb 3 cytochrome c oxidases are distant members of the superfamily of heme copper oxidases. These terminal oxidases couple O2 reduction with proton transport across the plasma membrane and, as a part of the respiratory chain, contribute to the generation of an electrochemical proton gradient. Compared with other structurally characterized members of the heme copper oxidases, the recently determined cbb 3 oxidase structure at 3.2 Å resolution revealed significant differences in the electron supply system, the proton conducting pathways and the coupling of O2 reduction to proton translocation. In this paper, we present a detailed report on the key steps for structure determination. Improvement of the protein quality was achieved by optimization of the number of lipids attached to the protein as well as the separation of two cbb 3 oxidase isoenzymes. The exchange of n‐dodecyl‐β‐d ‐maltoside for a precisely defined mixture of two α‐maltosides and decanoylsucrose as well as the choice of the crystallization method had a most profound impact on crystal quality. This report highlights problems frequently encountered in membrane protein crystallization and offers meaningful approaches to improve crystal quality.